2021
DOI: 10.1021/acsaem.1c01000
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalate@ZIF Induced CoWO4/WS2@C-N Nanoflower as a Highly Efficient Catalyst for Zn–Air Batteries

Abstract: It is crucial to cultivate competent and stable bifunctional electrocatalysts for both the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER). In this work, a high-performance and long-lasting electrocatalyst of CoWO4/WS2@C-N nanocomposite with the unique hierarchical flowerlike superstructure is achieved by sulfuration of porous polyoxometalate@ZIF-67 precursor, in which the polyoxometalate acts as both template and acidic etching agent. The introduction of polyoxometalate also plays a ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…This impediment has been partly alleviated by interfacing WS 2 with carbon nanotubes (CNTs), doping its lattice with first row transition metals (especially Co) or furnishing composite materials with OER active compounds (e. g., CoWO 4 ). [7][8][9][10] In the context of combining WS 2 with transition metals, a handful of works reporting the electrocatalytic activity of WS 2 involve the use of Ni, a first-row transition metal with good electrical conductivity and higher abundance in nature compared to its more commonly used counterpart Co. [11][12][13][14] In that manner, Ni has been employed as the working electrode (e. g., Ni foam), the scaffold where WS 2 is grown or even as oxide in the form of nanoparticles, leading to OER catalytically active species. The benchmark catalysts for HER and OER are Pt/C and RuO 2 / IrO 2 respectively, that is, catalysts based on noble metals.…”
Section: Introductionmentioning
confidence: 99%
“…This impediment has been partly alleviated by interfacing WS 2 with carbon nanotubes (CNTs), doping its lattice with first row transition metals (especially Co) or furnishing composite materials with OER active compounds (e. g., CoWO 4 ). [7][8][9][10] In the context of combining WS 2 with transition metals, a handful of works reporting the electrocatalytic activity of WS 2 involve the use of Ni, a first-row transition metal with good electrical conductivity and higher abundance in nature compared to its more commonly used counterpart Co. [11][12][13][14] In that manner, Ni has been employed as the working electrode (e. g., Ni foam), the scaffold where WS 2 is grown or even as oxide in the form of nanoparticles, leading to OER catalytically active species. The benchmark catalysts for HER and OER are Pt/C and RuO 2 / IrO 2 respectively, that is, catalysts based on noble metals.…”
Section: Introductionmentioning
confidence: 99%
“…A multimeter test showed that a USPC-based ZAB retained a steady open-circuit voltage of 1.43 V (Figure b, inset). As shown in Figure c, there was a very small voltage value gap between the charge and the discharge, indicating the high reversible energy conversion efficiency of the battery …”
Section: Resultsmentioning
confidence: 96%
“…As shown in Figure 5c, there was a very small voltage value gap between the charge and the discharge, indicating the high reversible energy conversion efficiency of the battery. 53 Figure 5d presents the polarization and power density curves for the as-obtained ZAB. The USPC catalyst showed a current density of 275 mA/cm 2 and a peak power density of 167 mW/ cm 2 , superior to the Pt/C catalyst (240 mA/cm 2 and 144 mW/ cm 2 ).…”
Section: Evaluating the Orr Performance Of The Differentmentioning
confidence: 99%
“…Here, the Keggin-type cluster H 3 PW 12 O 40 was encapsulated in ZIF-67 framework (Co 2+ source), and sulfuration under N 2 atmosphere, in the presence of thiourea, resulted in the formation of CoWO 4 /WS 2 @C−N nanoflowers. 17 The necessity of carbon-neutral fuels has increased significantly in recent years due to increasing environmental and economic considerations worldwide. Along with the traditional renewable energy sources, the water splitting (WS) reaction has emerged as a clean, sustainable energy source.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This kind of framework allows enhanced stability of CoWO 4 , facilitating OER. 17 Furthermore, due to the abundance of W and O in the system, the possible formation of WO 3 during the calcination process was also considered. Due to the facile transition between W 6+/5+/4+ , WO 3 can exhibit high oxygen-storage capacity and a reversible exchange of surface oxygens, making it a promising candidate for OER electrocatalyst.…”
Section: ■ Introductionmentioning
confidence: 99%